Structure and blood supply of motion neuro-muscles endings of skeletal muscles of rats of a different age. - Popel, S. L. (Морфологія / Morphologia / Morfologìâ, 2012)
Purpose of work consists in the study of structure of the neuro-muscles endings and their blood supply in ontogenesis. It is shown that at the level of the neuro-muscles endings there is the expressed blood-nerve barrier which is determined by the structural features of wall of blood microvessels. In the early period of ontogenesis of structure of blood-nerve barrier immature, and his functional insufficiency is compensated by made distance of sources of blood supply, that provides the sufficient morphological isolation of axons from albumens and cellular components of blood. With age structure of blood-nerve barrier destruction as a result of strengthening and generalization reverse development processes which pass by apoptos. Intracellulary alteration of neurolemocytes during ontogenesis testifies to their active trophic function, and concentration of synaps blisters in the cytoplasm of separate terminals neurolemocytes requires сomprehension of their role in functioning of blood supply barrier at the level of neuro-muscles endings.